MaCon: Consistent Cross-Disciplinary Conception of Manufacturing Systems. Issue 12 (2016) - Hackenberg, Georg; Gleirscher, Mario; Stocker, Thomas; Richter, Christoph; Reinhart, Gunther
Abstract: Conceptual designs of manufacturing systems contain input from all engineering disciplines involved in the life cycle of such systems. For their efficient and consistent conception, information about the elements of a conceptual design and their relationships have to be sufficiently precise but preferably abstract. We employ a cross-disciplinary modeling technique to capture this information together with consistency checking including simulation to accomplish such a challenging task. In this paper, we demonstrate our approach with a tool prototype. Based on an industrial example, we highlight how the features of the tool prototype can effectively support tasks in conceptual design. To illustrate this effectiveness, we visualize the modeling work flow and the results of the consistency checks based on data collected during tool usage.